Veratrilla baillonii Franch alleviate the symptoms of diabetes in type 2 diabetic rats induced by high-fat diet and streptozotocin - Chunlan Yan; Zhihao Zhang; Liqun Ma; Xinyi Xu; Muhammad Azhar; Xianju Huang; Jianxun Shi; Jun Li (Food Science and Human Wellness)
Our previous research studies have shown that Veratrilla baillonii Franch, a food supplement used by ethnic minorities in Southwest China, has multiple pharmacological activities, such as detoxif ication, antiinflammatory, antioxidant, and anti-insulin resistance. However, the detailed signal pathways for its salutary effect on damages in multiple organs due to type 2 diabetes mellitus (T2DM) remains unclear. The current study is to evaluate the therapeutic effects of V. baillonii on T2DM rats and to explore the underlying mechanisms. The T2DM rat model was successfully established by a high-sugar and high-fat diet (HFD) combination with intraperitoneal injection of a small dose of streptozotocin (STZ, 35 mg/kg). Biochemical analysis and histopatholgical examinations were conducted to evaluate the anti-diabetic potential of water extracts of V. baillonii (WVBF). The results showed that the WVBF treatment can improve hyperglycemia and insulin resistance, ameliorate the liver, kidney and pancreas injuries via decreasing inflammatory cytokines such as IL-6 and TNF-α, and oxidative damages. Further investigation suggested that WVBF modulates the signal transductions of the IRS1/PI3K/AKT/GLUT4 and AMPK pathways. These f indings demonstrate potentials of WVBF in the treatment of T2DM and possible mechanisms for its hepatoprotective activities.